The striker [compact disc, unabridged] - Cussler, Clive (Cussler, Clive. Isaac Bell novels., 2013)
The latest of the Isaac Bell adventure series. It is 1902, and a bright, inexperienced young man named Isaac Bell, only two years out of his apprenticeship at the Van Dorn Detective Agency, has an urgent message for his boss. Hired to hunt for radical unionist saboteurs in the coal mines, he is witness to a terrible accident that makes him think that something else is going on, that provocateurs are at work and bigger stakes are in play.